ANALISIS POTRET PENERAPAN PERDA Vs PERDA BERMASALAH PAJAK DAN RETRIBUSI DI KALIMANTAN (Studi Kasus di Provinsi Kalimantan Tengah dan Kalimantan Selatan) - Fani Heru Wismono (Jurnal Borneo Administrator, 2009)
The important thing in the implementation of regional autonomy is there is freedom of local governments (discretionery power) to carry out self-government on the basis of initiative, creativity and role-and active community in order to develop and promote the area. Authority of local governments to run some matters that is set in a regulation called “Perda” (local government regulation). In the framework of orderly administration and increasing the quality of the local government regulation product, required a process of the preparation procedure or regulation to be more effective and coordinated, that is the need to Understand the Design Guidelines of Local Government Regulations which have some perspective on: Tax and Retribution, Human Rights, Gender Equality, Development sustainability, etc., making it easier to do the evaluation and monitoring. Besides the need to prepare a script of academic (academic draft). Active community involvement and capacity building of legal drafter is a must if local government want to improve the regulation to be better quality.  Key words: local government regulation, regional autonomy, local government